Digital Transformation in MSMEs: How FinTech Adoption and Financial Literacy Drive Financial Resilience and Growth - Burhanuddin Burhanuddin; Ekayani Burhanuddin; Yusran Yusran; Yuniarni Yuniarni; Alda Faradillah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study investigates the critical drivers of financial resilience and sustainable growth among Micro, Small, and Medium Enterprises (MSMEs) in emerging economies. The primary problems identified within the MSME sector are low financial literacy, poor bookkeeping standards, and an adaptive resistance to digital financial technologies (FinTech), which collectively trigger severe operational vulnerability. The objective of this research is to evaluate the direct impact of financial literacy and FinTech adoption on MSME financial resilience, alongside exploring the mediating role of structured financial risk management. Utilizing a quantitative approach, structural equation modeling via SmartPLS was applied to analyze data gathered from 150 registered MSME owners and managers. The empirical findings demonstrate a highly significant positive correlation: advanced financial literacy and robust FinTech integration drastically accelerate the establishment of institutional financial resilience. Furthermore, the synthesis reveals that financial risk management acts as a powerful mediating variable that mitigates cognitive dissonance and operational bottlenecks. In conclusion, combining financial literacy with digital infrastructure provides a scalable strategic framework that transitions MSMEs from structural vulnerability to digital-era resilience and long-term sustainability.